Impact of Coal-Fired Power Plants on Suspended Sediment Concentrations in Coastal Waters - Zhi-Cheng Huang; Po-Chien Lin; Po-Hsun Lin; Shun-Hsing Chuang (Journal of Marine Science and Engineering)
Many coastal coal-fired power plants utilize seawater flue gas desulfurization (SWFGD) systems, which may pose risks of heavy metal attachment on suspended sediments. Understanding variations in suspended sediment concentration (SSC) is therefore useful for controlling marine pollution. We studied two power plants as examples of discharging SSC using continuous measurement techniques. Monitoring sites at intake and discharge points and the surrounding coastal areas of the power plants was conducted across seasons. The first case study, Linkou Power Plant, is located in a high-SSC region influenced by monsoon winds and wave activity. Results indicate that SSC levels at all the monitoring sites are correlated with environmental factors of wind and wave conditions, with strong positive correlations observed between the intake and discharge points. In contrast, the Dalin Power Plant is located within an international harbor, where the SSC levels are generally low; however, sudden increases in SSC are observed at the intake point due to disturbances from vessel activities. These sudden increases are not evident at the discharge point, suggesting a sink of SSC may occur within the system. These results demonstrate that the two studied power plants have limited effects on the increase in SSC; the SSC in the discharge point is mainly related to the SSC input at the intake point. Effective management of SSC at the intake may help mitigate coastal pollution caused by SSC discharge and reduce the risk of harmful substances adhering to suspended solids in the discharging wastewater.